Membangun Dialog dalam Keberagaman: Memahami Ritual Martutu Aek Batak Toba dan Sakramen Baptis - Sigalingging, Jimson (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2020)
Religion and culture are two different things. Religion is God’s creation, while culture is human creativity. However, the two of them are interconnected and inseparable. The focus of this study is the understanding of the martutu aek ritual in connection to the Sacrament of Baptism. Martutu aek is a ritual of purification of babies from evil spirits before they are formally accepted into the society. Meanwhile, the Sacrament of Baptism is one of the sacraments of initiation in the church. This study contains the meaning of martutu aek; the basic implementation, function, and meaning of the sacrament of baptism, and its purpose according to the Catholic Church. The methodology used in this research is a comparative theological study. The findings of this study uncover the similarities and differences between the ritual of martutu aek of Batak Toba and the meaning of the Sacrament of Baptism. The contribution of this research is to build a religious dialogue within the Batak Toba communities.